Some implications of an alternative structure for DNA. - Sasisekharan, V (1978)
We have constructed a space-filling (Corey-Pauling-Koltun) model of an alternative structure for DNA. This structure is not a double helix, but consists of a pair of polynucleotide strands lying side by side and held together by Watson-Crick base pairing. Each of the two strands has alternating right- and left-handed helical segments approximately five base pairs in length. Sugar residues in alternating segments along a strand point in opposite directions. A structure slightly different from the present one proposed earlier by ourselves and another group and in which sugars in a strand all point in the same direction is ruled out. The present structure yields natural solutions to the problems of supercoiling of DNA and of strand separation during DNA replication. This model is energetically more favorable than the double helix.